Expression of flu gene in Ciprofloxacin resistant uropathogenic Escherichia coli - Ahmed, Suaad Ali; Flayyih, May Talib (Iraqi Journal of Science, 2025)
Uropathogenic E. coli (UPEC) exhibits various virulence factors that enable it to both establish itself in the urinary tract and trigger disease symptoms. Ag43, which is encoded by the flu gene, promotes bacterial adherence and the production of biofilms on human urothelial cells. Using the Kirby-Bauer method, the ciprofloxacin sensitivity of forty UPEC isolates was assessed. Twenty-two UPEC isolates (21 of which were resistant to ciprofloxacin and one of which was sensitive) were used in order to calculate the MIC of ciprofloxacin using the macro tube assay. Using the (ABIO pure extraction) procedure, genomic DNA was extracted from bacterial growth. Real time PCR (qRT-PCR) proved successful in detecting the expression of the flu gene. Antimicrobial susceptibility testing of UPEC isolates showed that 21 out of 40 isolates (52.5%) were resistant to ciprofloxacin. MIC for isolates resistant to ciprofloxacin was ≥ 64 (µg/ml). The identification of the flu gene by the analysis of PCR showed that (21/22; 95.45%) carried the flu gene. The findings of qRT-PCR revealed that (4/11; 36.3%) of the UPEC isolates had downregulation of the flu gene, whereas (7/11; 63.6%) showed overexpression. The flu gene (folding=5.59) had the highest expression in UPEC isolate number 3. A significant correlation was observed, with most UPEC isolates showing overexpression of the flu gene. Thus, the flu gene plays a crucial part in the pathogenicity of isolates from UPEC.